Determinantes na decisão de internacionalização : estudo de caso em um grupo australiano de varejo de moda - Alves, Carla Santin (2016)
The case study aimed to identify decision determinants on foreign retail company to internationalize. The research is based on the growing process of globalization nowadays that increasingly reduces the boundary between countries and allow companies to seek new markets, as well as the need for further studies within the retail sector taking into account all its specificities and characteristics. The chosen theory for the study is the Eclectic Paradigm, which states that companies will internationalize if they have ownership location and internalization advantages. The preference for this theory resides on its application to specific retail market and the importance of the process in the vision of the invested country and the investor. The research is exploratory on its objectives, it is a case study on its procedures and has a qualitative approach. The case study although unique is integrated, once it involves more than one unit of analysis. The case unit is an Australian fashion retail company founded in the early nineties, privately held, which operates in seventeen countries and mainly through its owned stores. The company entry movements were grouped into seven groups of internationalization that were evaluated through analysis of documents, internal files, interviews and direct documentation. Five interviews were held with executives and company managers for more detailed processes. The research results demonstrate adherence to the theory used and the business focus of the case study and identified the determinants for the company‟s internationalization as market positioning through the offer of quality and affordable products to the general population, the maintenance of the business culture in the new markets, the entrance into markets with similar characteristics as the Head Office‟s, growing markets and predominantly young population with fashion interests, and reduced operating costs. A framework was structured based on the findings.